Rhythms of the Pachakuti : Indigenous Uprising and State Power in Bolivia - Gutierrez Aguilar, Raquel (Book collections on Project MUSE., 2014)
In Rhythms of the Pachakuti, Raquel Gutierrez Aguilar documents a series of popular indigenous uprisings against the country's antidemocratic policies, tracing the internal dynamics of such disruptions to consider how motivation and execution incite political change.